The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.tranon.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Proteomics Exploration of Melanoma Identifies Proteins in Serum with Associations to T-Stage and Recurrence

Abstract: BACKGROUND: Blood-based proteomic profiling may aid and expand our understanding of diseases and their different phenotypes. The aim of the presented study was to profile serum samples from patients with malignant melanoma using affinity proteomic assays to describe proteins in the blood stream that are associated to stage or recurrence of melanoma. MATERIAL AND METHODS: Multiplexed protein analysis was conducted using antibody suspension bead arrays. A total of 232 antibodies against 132 proteins were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The search for biomarkers of melanoma progression and response to therapy including recent genomics or other “omics” approaches has led to the discovery of numerous promising proteins (reviewed in (Gowda et al., 2020; Rodriguez‐Cerdeira et al., 2018)). However, none of these potential biomarkers have been validated so far, and only soluble lactic dehydrogenase (sLDH) remains as the protein that correlates with the disease burden in some patients with metastatic melanoma (Byström et al., 2017). Recent attempts at establishing correlations between levels of sLDH and any specific molecular, immunological or metabolic phenotypes, including immune cell infiltrate in the tumour, point mutations, DNA copy number, promoter methylation, RNA expression or protein expression in melanoma metastases have been not been successful (Gowda et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for biomarkers of melanoma progression and response to therapy including recent genomics or other “omics” approaches has led to the discovery of numerous promising proteins (reviewed in (Gowda et al., 2020; Rodriguez‐Cerdeira et al., 2018)). However, none of these potential biomarkers have been validated so far, and only soluble lactic dehydrogenase (sLDH) remains as the protein that correlates with the disease burden in some patients with metastatic melanoma (Byström et al., 2017). Recent attempts at establishing correlations between levels of sLDH and any specific molecular, immunological or metabolic phenotypes, including immune cell infiltrate in the tumour, point mutations, DNA copy number, promoter methylation, RNA expression or protein expression in melanoma metastases have been not been successful (Gowda et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Factors known to be involved in angiogenesis, immune suppression, modification of stroma, capture of cancer cells in lymph nodes and tumour cell progression have been identified in sEV from the plasma of melanoma patients by us and others (Alegre et al., 2016; Gowda et al., 2020; Hood, 2019; Sharma et al., 2020). Several previous studies suggested that the use of EV, especially tumour cell‐derived sEV (TEX), might be a more promising approach to the discovery and development of melanoma‐associated biomarkers than strategies dependent on conventional tumour tissue examination or on measuring levels of soluble factors in patients’ plasma (Byström et al., 2017; Rodriguez‐Cerdeira et al., 2018; The TCGA Research Network).…”
Section: Discussionmentioning
confidence: 99%
“…This method has previously been applied in both pediatric and adult cohorts in other contexts such as childhood asthma and malaria, [12,30] liver and kidney disease, [11,31] nervous system/neurodegenerative disease, [32,33] and cancer. [34] Although our study included a large number of children, the number of children per lifestyle group was too small to allow for analysis stratified by exposure, such as vaccination and breast feeding or outcome such as sensitization to allergens. An association with sex in the development of plasma proteins cannot be ruled out; however, the proportions of females and males were reasonably balanced, also between the lifestyle groups (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This method has previously been applied in both pediatric and adult cohorts in other contexts such as childhood asthma and malaria, [ 12,30 ] liver and kidney disease, [ 11,31 ] nervous system/neurodegenerative disease, [ 32,33 ] and cancer. [ 34 ]…”
Section: Discussionmentioning
confidence: 99%
“…The expression of S100A6 was described in cutaneous and extracutaneous lesion including melanocytic nevi and malignant melanoma [179]. S100A6 is overexpressed in Spitz nevi, melanocytic nevi, and melanomas [160]; in fact, tissue analysis of melanoma patients revealed that most melanomas showed positive staining for S100A6 [161]. Interestingly, many studies have suggested a role of S100A6 in metastasis, although the exact metastatic mechanism is not specified.…”
Section: S100a6mentioning
confidence: 99%